THE EFFECT OF COMPANY SIZE AND FINANCIAL PERFORMANCE ON EARNINGS MANAGEMENT: (Empirical Study of Mining Companies Listed on the Indonesia Stock Exchange for the Period 2016-2021) - Zeninah Alsavina; Endah Finatariani (Transpublika Publisher, 2023)
In the context of the expanding economy in Indonesia, the management of companies faces increased competition, necessitating effective strategies to stay competitive. Financial reports play a crucial role in evaluating a company's performance and aiding decision-making processes for both management and investors. Among the essential elements used to assess management performance in financial statements is profit, presented in the profit/loss statement. This study aims to provide empirical evidence on the effect of firm size and financial performance, proxied by profitability and leverage, on earnings management in mining companies listed on the Indonesia Stock Exchange during the period of 2016-2021. The research adopts a quantitative approach and utilizes secondary data from the selected mining companies. The population comprises mining companies listed on the Indonesia Stock Exchange, and the sample is obtained through purposive sampling, resulting in 66 data points from 11 companies over a 6-year period. Data analysis involves multiple linear regression, descriptive statistical tests, panel data regression model analysis, Common Effect Model selection test, classical assumption test, and multiple linear testing using Eviews version 11 for data processing. The research findings indicate that when considered together, Company Size and Financial Performance, represented by Profitability and Leverage, have a significant impact on Earnings Management. Specifically, Financial Performance, proxied by Profitability, is found to exert a notable effect on Earnings Management. However, the study reveals that Firm Size and Financial Performance, proxied by Leverage, do not significantly influence Earnings Management.